Pemanfaatan Media Whatsapp Grup dalam Proses Pembelajaran pada Masa Pandemi Covid-19 di MI Al-Fadliliyah Darussalam Ciamis - Selamet Selamet; Mohammad Erihadiana; Qiqi Yuliati Zaqiah (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Since Indonesia announced that it had been exposed to COVID-19 on March 16, 2020, all forms of activities that trigger social activities were freely dismissed with various Social Distancing, Physical Distancing, and PSBB (large-scale social restrictions) policies. Many sectors are affected by this policy, including the education sector. The Minister of Education and Culture who established online learning (on the network) with an emergency curriculum that he published made learning a little different from usual. There is no face-to-face in the classroom directly and learning is transformed by distance learning that works with parents at home in active communication. The continuity of this learning depends on the teacher providing the material in its implementation, assisted and monitored by the parents of each student. By using whatsapp group media in learning during the COVID-19 pandemic, it is one of the efforts made by teachers in seeking an effective and fun learning. MI Al-Fadliliyah Darussalam continues to strive and is committed to optimally implementing online learning, the teacher's role is very important in the KBM it carries out. The use of whatsapp group media is the most popular media to facilitate long-distance communication, therefore online learning uses this media more often, because it is easier and better known in the community, especially parents. However, of course not only using whatsapp group media is not the end of the online learning solution. There needs to be a strategy and review related to the problems that occur to parents of students. Keywords: WhatsApp group media utilization, learning and the COVID-19 pandemic